Chapter 4 offer regulation under the 2008 Companies Act - Labuschagne, Frederik J. (University of Pretoria, 2014)
Chapter 4 of the Companies Act of 2008 aims to regulate offers to the public of securities and is reviewed against the principles which underscore the regulation of offerings. An overview of the historical development of the company which is parallel to the regulation of securities shows the crystallized principles which are compared against the development and enactment of the current regulatory regime. The concept of “complete law” as key element to effective regulation is discussed and applied in the review of Chapter 4 determining the effectiveness of the dispensation. The three determining concepts of regulation: the “offer,” “securities” and “public” are studied against the definitions which determine regulation and the inclusion of secondary market regulation of unlisted securities. Serious shortcomings in the process are identified. These errors, together with the practical problems of defining and regulating the secondary market in Chapter 4 read with the remainder of the delineating definitions, concludes that the current system is not in line with the principles of regulation and the Grundnorm of fraud prevention, resulting in Chapter 4 falling under the concept of “incomplete law” resulting in a high probability of enforcement failure and inefficiency. A comparative overview related to the jurisdictions of the United Kingdom and the United States follows with recommendations aimed at amending Chapter 4 relating to the regulatory regime in toto as well as the regulation of unlisted securities in the secondary market.
URI: https://repository.up.ac.za/handle/2263/45981
Keywords: Companies Act; Offer regulation